Analisis Pemahaman Akuntansi Pajak, Kesadaran Wajib Pajak, dan Kepatuhan Wajib Pajak : Studi Kasus pada UMKM Kota Bandung Sub Unit Dinas Koperasi dan UMKM Kota Bandung - Anita, Dian; Agustine, Albi (CV. ULIL ALBAB CORP, 2025)
Taxpayer compliance is one of the important factors in optimizing tax revenue, especially for Micro, Small, and Medium Enterprises (MSMEs). However, in Bandung City, there are still many MSMEs who have a low understanding of tax accounting and suboptimal tax awareness, which has an impact on low levels of compliance. This study aims to analyze the understanding of tax accounting, taxpayer awareness, and taxpayer compliance among MSMEs in Bandung City. This research method uses a qualitative approach with descriptive methodology. The results of the study indicate that the understanding of tax accounting among MSMEs is still low due to limited access to information and lack of education about taxation. In addition, taxpayer awareness also varies, where some MSMEs understand the importance of paying taxes but face financial and administrative constraints. Other factors found to influence tax compliance are the complexity of tax regulations, limited resources, and perceptions of government policies. Overall, this study shows that increasing education and simplifying the tax process can be a solution to improving tax compliance in the MSME sector.